Which do you prefer, OCT or IVUS?. Issue 2 (21st July 2015) - Tobis, Jonathan
Key Points: OCT has higher resolution than IVUS. This study compared the measurements of lumen and stent diameters from IVUS or OCT but the images were chosen by the 11 observers so that the exact same images were not measured. The standard deviation of the measurements is tighter with OCT images. The absolute difference in measurements was small. This may be clinically insignificant, but operators may feel that it is easier to measure stent size from the OCT images.